Perspektif Hadits Bukhari Muslim No. 1407 dan Pasal 3 UU No. 23 Tahun 2011 tentang Pengelolaan Zakat - Andika, Indra Dwi Cahya; Arifin, Tajul (Journal of Literature Review, 2025)
This study aims to analyze the role of zakat from an Islamic perspective, with an emphasis on the teachings of the Hadith and applicable legal regulations. The methodology used in this study is a normative legal approach based on religious texts, especially the Hadith of Bukhari Muslim No. 1407, as well as regulations governing the management of zakat, namely Law No. 23 Article 3 of 2011. In addition, this study also examines how zakat can function as a tool to improve community welfare. The results of the study indicate that zakat can have a significant social impact if managed properly, and not simply considered an obligation. This study concludes by emphasizing the importance of collaboration between religious teachings and legal regulations in the management of zakat to achieve broader welfare goals.